Comparative development of India and China - Chen, Kuan-I.; Uppal, J. S. (New York : Free Press; London : Collier-Macmillan, 1971)
This is a comparative study of economic development in India and China. It provides scholarly writings from specialists that focus on the problems and processes of development in the two countries. The volume covers: emerging patterns in economic development; development policy and planning techniques; demographic patterns and population policy; capital formation and development of human resources; and international economic relations-trade and aid.
Title on spine: India and China.
Includes bibliographical references: p. 401-404.
lje 26/09/2018
Loans
Keywords: Economic development; Economic conditions; India; China